An empirical analysis of the determinants of credit risk in Chinese banking sector - Fanyue, Li (2018)
Abstract For banking sector, credit risk is the main risk since the main business for banks is loans. And loans will bring about the problem of credit risk. Non-performing loans can be used as an indicator to measure this kind of credit risk. China, as a developing country, is the second economic utility all over the world. In this dissertation, we try to use some bank-specific variables and macroeconomic variables to measure non-performing loans in China during the period from 2011 to 2017.